Another hotel on route 62 : room for a niche? - van der Hoven, Chris; Townsend, Stephanie (London : Wits Business School, 2018)
In late 2017, Wits Business School MBA student, Bulelani Moyo, pondered all the information he had gathered for a proposal he was considering putting to Jeff Miller, CEO of South African venture capital company Grovest, for investing in a new and innovative hotel concept in three locations on Cape Route 62 (Route 62), a tourist route covering parts of the Western Cape and Eastern Cape. He believed that there could be scope for a disruptive hotel model on that route. However, for such a hotel to be viable, it was crucial to target the right audience. Moyo was contemplating whether there were opportunities in four customer segments: the "ageing biker", the "millennial adventurer", the "foreign road-tripper" and the "travelling salesman". As he read through his research, he wondered whether he had enough to be able to make a convincing case for any of these markets to Miller.
Originally Published Invan der Hoven, C., & Townsend, S. (2018). Another hotel on Route 62: Room for a niche? WBS-2018-3. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Proposal writing in business -- Case studies; Hotels -- South Africa -- Western Cape -- Marketing -- Case studies; Hotels -- South Africa -- Eastern Cape -- Marketing -- Case studies; Target marketing -- South Africa -- Western Cape -- Case studies; Target marketing -- South Africa -- Eastern Cape -- Case studies